Prospective Evaluation of 18-Fluoro-2-Deoxy-D-Glucose Positron Emission Tomography for the Discrimination of Paraaortic Nodal Spread in Patients With Locally Advanced Cervical Carcinoma. Issue 1 (1st January 2013) - Perez-Medina, Tirso; Pereira, Augusto; Mucientes, Jorge; García-Espantaleón, Manuel; Jiménez, Jesús S.; Calles, Laura; Rodríguez, Begoña; Iglesias, Enrique
Abstract : Main Objective: Patients with locally advanced cervical cancer (LACC) are usually treated with concurrent chemoradiotherapy. Extended-field chemoradiotherapy is indicated in cases of paraaortic nodal spread. Nowadays, 18-fluoro-2-deoxy-D-glucose positron emission tomography (FDG-PET) is considered to be the most accurate image method of detection of node or distant metastases. The goal of this study was to evaluate the accuracy of FDG-PET for detecting paraaortic lymph node (PALN) spread in patients with LACC. Methods: Patients with LACC from 2 tertiary university hospitals in Madrid, Spain, were submitted to a laparoscopic infrarenal PALN dissection after FDG-PET evaluation. Based on pathologic results as gold standard, sensitivity, specificity, and positive and negative predictive values of FDG-PET were calculated thereafter for PALN metastasis. Results: A total of 52 patients with LACC fulfilled the inclusion criteria. All of them underwent a laparoscopic infrarenal paraaortic lymphadenectomy. Eighteen patients (34.6%) had pathologically proven PALN metastases. Among them, 4 (12.5%) had negative FDG-PET (false negatives). Furthermore, 2 positive FDG-PET patients were not affected after histologic analysis (11.1% false positives). No complications occurred in our series. Sensitivity, specificity, and positive and negative predictive value of the FDG-PET were 77.7, 94.1, 87.5, and 88.9, respectively, for the detection of PALN metastases. Conclusions: The sensitivity and specificity of FDG-PET remains limited, so PALN dissection should be part of the pretherapeutic staging in every patient with LACC before definitive concurrent chemoradiotherapy.